Nepal’s Climate Diplomacy: Key Takeaways - Khanal, Bharat (Journal of Environment Sciences, 2025)
This study explores the contours of Nepal’s climate diplomacy mostly focusing on climate emergency, vulnerabilities and it’s, strategies, and role in global climate negotiations. Despite contributing minimally to global greenhouse gas emissions, Nepal ranks among the most climate-vulnerable nations. The research employs a multidisciplinary approach, combining quantitative content analysis with case studies, to provide actionable insights for Nepal. The research highlights Nepal’s efforts to integrate climate action into national policies, advocate for climate justice, and leverage its geographical position to promote global action. By analyzing past climate negotiations, successful models from other countries, and Nepal’s domestic policies, the study suggests a robust framework for enhancing its climate diplomacy. Key findings emphasize the importance of regional collaboration, science diplomacy, and equitable climate finance and improving domestic climate governance framework.